Effect of various acupuncture courses for upper limb motor dysfunction after ischemic stroke: a Bayesian network meta-analysis - Wang, Can; Yu, Pei; Tang, Yuqi; Liu, Yaning; Shi, Jiangwei; Yang, Xuhui; Yin, Zihan; Zhao, Ling (Frontiers in Aging Neuroscience, 2025)
BackgroundAcupuncture has been widely used in the treatment of post-ischemic stroke upper limb motor dysfunction (PIS-ULMD). However, previous studies have reported substantial variability in acupuncture courses, and the lack of a clearly defined optimal course has impeded further improvement in therapeutic outcomes. Studies show that treatment course is a key factor in acupuncture’s dose-effect relationship. The Specification of Formulation and Evaluation for the Clinical Practice Guideline of Acupuncture and Moxibustion [CAAM-2019(001)], issued by the China Association of Acupuncture-Moxibustion (CAAM), points out that current domestic acupuncture clinical practice guidelines lack evidence-based temporal parameters, resulting in clinicians’ reliance on personal experience and inconsistent treatment outcomes. Herein, we conducted network meta-analysis to compare the effectiveness of diverse acupuncture courses for PIS-ULMD treatment.MethodsTen databases were searched from their inception to March 21, 2025. Randomized controlled trials (RCTs) on acupuncture for PIS-ULMD were screened. The Cochrane Collaboration Risk of Bias (RoB 2) tool was used to assess the risk of bias in the included studies. The primary outcome was the change in the Fugl-Meyer Assessment-Upper Extremity (FMA-UE) scale before and after treatment. All meta-analysis was performed using RevMan 5.3, STATA (V14.0) and Aggregate Data Drug Information System (ADDIS) (V1.16.6). The Grading of Recommendations Assessment, Development and Evaluation (GRADE) system was applied to evaluate the quality of evidence for each outcome measure.ResultsA total of 67 RCTs involving 5,635 PIS-ULMD patients were included. The pairwise meta-analysis indicated that acupuncture combined with conventional therapy resulted in higher FMA-UE scores compared to conventional therapy alone (n = 5,635; MD = 6.95, 95% CI: 5.89–8.00). Network meta-analysis results recommended that 8-week acupuncture course is the most effective acupuncture course. However, the evidence quality was low to critically low.ConclusionAcupuncture combined with conventional therapy significantly improves upper limb motor function in PIS-ULMD patients. For enhancing upper limb motor function, an 8-week acupuncture regimen may be more appropriate, particularly for patients in the subacute phase and severe PIS-ULMD. However, the overall evidence quality was low, it is recommended additional well-designed RCTs with larger sample sizes to validate these findings.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/, Identifier CRD420251022808.